UNI-FIED ACCOUNTING. - Raby, William L. (The Accounting Review, 1954)
The article focuses on the concept of uni-fied accounting. The accounting problems of small and medium-size business cannot be solved by gimmicks. The techniques used in many large firms are still too costly, too experimental, too dependent upon a degree of routinization not yet achieved to be adaptable to the needs of small and medium-size business. It is in this area that the concepts of what has been termed Uni-fied or Simplified Unit Accounting have developed. Production costs were reduced in our factories, and distribution costs in wholesale and retail establishments, through utilizing certain techniques. In production, a basic technique has been to use a minimum number of uniform parts to form a maximum number of differentiated products. Both process and product have been organized to this end. In both areas, a certain degree of work organization and specialization of functions has helped cut cost. The concepts of Uni-fied accounting are merely a restatement of concepts utilized in manufacturing and distribution.